A conduct parameter model of price discrimination. (23rd May 2017) - Kutlu, Levent
Abstract: We consider a conduct parameter model where firms price discriminate based on the consumers' willingness to pay. For any conduct, the average price is invariant to the extent of price discrimination. Moreover, when the number of prices goes to infinity, there is a linear relationship between market power, measured by conduct, and range of offered prices. Hence, when the firms face competition, some of the high valuation customers are charged below their valuations, which contrasts with perfect price discrimination results for a monopoly.